Treating Urothelial Bladder Cancer (Springer International Publishing, 2018)
This book aims to bring together the current research and discussions surrounding bladder cancer management. New technologies and therapeutic agents have become increasingly effective at treating urothelial bladder cancer and have created a range of opportunities to change the ways in which the disease is treated. Chapters cover the changes in adjuvant treatment, confocal laser endomicroscopy, and the roles of oncologists, pathologists, and radiotherapists in managing bladder cancer. Treating Urothelial Bladder Cancer is particularly relevant to urologists, oncologists, and radiotherapists, but is also applicable to practitioners, geriatricians, and public health managers due to its multidisciplinary approach to bladder cancer management.